Handling of Complaints on Shipping Services by Public Relations of the Juanda Customs and Excise Type Middle Customs Office - Suprihatin; Fuad Fauzi; Ratna Puspita Sari; Aulia Afniar Rahmawati; Edelweis Putri Prima (Universitas Kapuas Sintang, 2025)
The number of complaints about shipping services carried out by the Office of Supervision and Services of the Customs Madya Type (KPPBC TMP) Juanda has received special attention from the leadership because it affects the institution's image. In public relations, in this case, the Information Counseling and Services Section (P.L.I.) is required to solve the problem. The study aims to determine the role of KPPBC TMP Juanda Public Relations in handling complaints related to shipping services. The method used in this research is a qualitative method with a descriptive approach to describe how consumer complaints are responded to and managed by analyzing information and information from employees in charge of shipping goods services and employees assigned to the P.L.I. Section. Additional information was obtained from observing the agency's social media. The results showed that the dominant complaints came from migrant workers as senders or their families as recipients of goods. Complaints are submitted through official channels and social media and can be accessed by the public. The public relations of KPPBC TMP Juanda has planned and implemented many programs to solve this problem. However, the same complaints still occur because the shipment goods service users are not regular users. In addition, the public relations department also needed help in delivering information to all levels of society. Keywords: Complaints, Public Relations, Services, Bea & Cukai